TV and entrepreneurship - Viktor Slavtchev; Michael Wyrwich (Friedrich Schiller University Jena, 2021)
This paper analyzes empirically whether individuals' decisions to start an own business can be influenced via television (TV). To identify its effect, we utilize exogenous regional variation in the availability of TV that conveyed images conducive to entrepreneurship and the notion that self-reliance, self-determination and proactive behavior are desirable from individual and social point of view. We use both regional-level as well as geo-referenced individual level data and show that the entrepreneurship incidence is higher among the residents of regions that had TV signal than in regions without TV, indicating a first-order effect on the directly exposed individuals. We find that the effect would fade out if only directly treated individuals are more likely to become entrepreneurs and the last exposed cohort becomes "too old". However, we also find that non-directly exposed successive cohorts and descendants of directly exposed individuals also wish to become entrepreneurs more often. We provide evidence that is consistent with second-order effects due to the intergenerational transmission of entrepreneurial mindset and suggests a formation of a self-sustaining entrepreneurial culture, which can cause long lasting differences between treated and non-treated population groups or regions.
Keywords: L26; J24; M13; P20; P30; O30; D02; D03; Z10; 330; Entrepreneurship; TV; Culture; Occupational choice